Novel missense mutations in exon 15 of desmoglein-2: role of the intracellular cadherin segment in arrhythmogenic right ventricular cardiomyopathy? - Gehmlich, K; Asimaki, A; Cahill, T; Ehler, E; Syrris, P; Zachara, E; Re, F; Avella, A; Monserrat, L; Saffitz, J; McKenna, W (2010)
BACKGROUND: The diagnosis of arrhythmogenic right ventricular cardiomyopathy can be challenging. Disease-causing mutations in desmosomal genes have been identified. A novel diagnostic feature, loss of immunoreactivity for plakoglobin from the intercalated disks, recently was proposed. OBJECTIVE: The purpose of this study was to identify two novel mutations in the intracellular cadherin segment of desmoglein-2 (G812S and C813R in exon 15). Co-segregation of the G812S mutation with disease expression was established in a large Caucasian family. Endomyocardial biopsies of two individuals showed reduced plakoglobin signal at the intercalated disk. METHODS: To understand the pathologic changes occurring in the diseased myocardium, functional studies on three mutations in exon 15 of desmoglein-2 (G812C, G812S, C813R) were performed. RESULTS: Localization studies failed to detect any differences in targeting or stability of the mutant proteins, suggesting that they act via a dominant negative mechanism. Binding assays were performed to probe for altered binding affinities toward other desmosomal proteins, such as plakoglobin and plakophilin-2. Although no differences were observed for the mutated proteins in comparison to wild-type desmoglein-2, binding to plakophilin-2 depended on the expression system (i.e., bacterial vs mammalian protein expression). In addition, abnormal migration of the C813R mutant protein was observed in gel electrophoresis. CONCLUSION: Loss of plakoglobin immunoreactivity from the intercalated disks appears to be the endpoint of complex pathologic changes, and our functional data suggest that yet unknown posttranslational modifications of desmoglein-2 might be involved.